PEMANFAATAN “KAHOOT” SEBAGAI MEDIA ASESMEN PADA MATA PELAJARAN PENDIDIKAN PANCASILA UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PESERTA DIDIK KELAS X SMA HANG TUAH 4 SURABAYA - Karunia Rahayu Nur Amina; Listyaningsih (Kajian Moral dan Kewarganegaraan, 2025)
Kahoot is an internet-based learning media that has a feature in the form of a quiz game. This study aims to test the use of "kahoot" as an assessment media that can improve student motivation and learning outcomes. This research method uses Quasi-Experimental Design. Researchers use the Posttest Only Control Design design so that the effect of treatment can be calculated by comparing the values ​​in the control class and the experimental class. Data collection techniques consist of giving tests through the kahoot application and student response questionnaires to the use of kahoot getting a percentage of 84% and initial learning motivation of 51% with fairly good criteria and final learning motivation of 86% with very good criteria. The data analysis technique used is a hypothesis test using the one sample t test formula. Based on the results of the one sample t test hypothesis test, the test score output obtained a sig. (2-tailed) value of 0.002 <0.05, with decision making if the sig value <0.05 then Ho is rejected and Ha is accepted, if the sig value> 0.05 then Ho is accepted and Ha is rejected. So it can be concluded that Ho is rejected and Ha is accepted because sig.(2-tailed) is 0.002 < 0.05, namely the use of Kahoot as an assessment medium can increase the motivation and learning outcomes of students in the Pancasila Education subject on the material of introducing norms in everyday life.